Urban motives in the work of Gregory Kvitka-Osnovyanenko - Петренко, Ольга Іванівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The paper contains the analysis of the system of urban images and motifs in the writings by Hryhory Kvitka-Osnovyanenko. It is commonly thought that the urbanism in the Ukrainian literature is synonymous with modernity, in contrast to the 19th century rusticism. However, the city in the previous epochs was already the surrounding for the development of the cultural industry. The analysis of the prose written by H. Kvitka-Osnovyanenko using urban studies shows a significant artistic level of understanding urban life as a mental image and as a social practice. The researchers of H. Kvitka-Osnovyanenko’s prose since the nineteenth century considered as the most important contribution his innovative for the Ukrainian literature idea to introduce a rural topic and depict the characters – natives from the village – not in the Burlesque register, as it was practiced before, but using means of a high poetic style. However, H. Kvitka-Osnovyanenko described not only rural life, but also the everyday life of inhabitants of cities and towns, their social practices and the constants of the urban imaginary. It is worth speaking about the reception of the baroque images of urban space in the prose of H. Kvitka-Osnovyanenko, especially the city as the embodiment of New Jerusalem («Kozyr-divka»); the urban topography of the hell («Ot tobi y skarb»), the travesty of constant monives in the description of the city («Konotopska widma»). In addition, the ideas of H. Kvitka-Osnovyanenko concerning the urban life were embodied in the writings of the next generation of romantic writers and realists – in particular, the opposition of the village as traditional space and the city as an assimilative one. The author examines several scenarios of self-realization of peasant characters in the city – from the successful realization of their plans to moral decline. H. Kvitka-Osnovyanenko points to different points of view, avoiding a strictly positive or negative attitude towards urban space.